Rethinking how volatiles are released from plant cells. (September 2015) - Widhalm, Joshua R.; Jaini, Rohit; Morgan, John A.; Dudareva, Natalia
Highlights: Modeling shows mM VOC levels must be present in membranes for emission to occur via passive diffusion. We suggest that biological mechanisms contribute to VOC emission and lower concentrations in membranes. The cuticle provides the highest resistance to VOC emission. Abstract : For plant volatile organic compounds (VOCs) to be emitted, they must cross membrane(s), the aqueous cell wall, and sometimes the cuticle, before moving into the gas phase. It is presumed that VOC movement through each barrier occurs via passive diffusion. However, VOCs, which are primarily nonpolar compounds, will preferentially partition into membranes, making diffusion into aqueous compartments slow. Using Fick's first law, we calculated that to achieve observed VOC emission rates by diffusion alone would necessitate toxic VOC levels in membranes. Here, we propose that biological mechanisms, such as those involved in trafficking other hydrophobic compounds, must contribute to VOC emission. Such parallel biological pathways would lower barrier resistances and, thus, steady-state emission rates could be maintained with significantly reduced intramembrane VOC concentrations.